THE USE OF GOOGLE TRANSLATE IN EFL ESSAY WRITING - Chandra, Sylvi Octaviani; Yuyun, Ignasia (LLT Journal: A Journal on Language and Language Teaching, 2018)
Writing skill is considered a difficult skill for some of the students because of limited vocabulary as well as grammatical weakness. Since the students face this problem, they often take a shortcut if they have a writing assignment, which is using Google Translate (GT). Many studies have focused on this translator to find out the error from GTs output and rarely discuss the way students utilize GT in their language learning. Therefore, this study aims to investigate further the practice of GT in EFL essay writing as wells as its role in language learning. The study was conducted in Universitas Kristen Krida Wacana, involving eight respondents from Ukrida Department of English. Two methods were used, such as mediated-observation and interview. A writing task was given to each respondent and her/his writing process was recorded using screen-recording application. The data collected from the writing task was analyzed by classifying it into appropriate writing aspect while the interview data were transcribed. The result showed that students used GT in three different aspects: vocabulary, grammar, and spelling. Vocabulary became the highest used, with word-level became the first one, followed by phrase as a second highest, and sentence as the third. Spelling became the fourth highest used, while grammar was the least used among students. It is also found out that GT is perceived as a dictionary as students used GT mostly in vocabulary.